A method for improving the electrochemical performance of NaTi2(PO4)3∥LiMn2O4 aqueous ion battery
By designing the mixed electrolyte of Li2SO4-Na2SO4-dodecyl sulfate, the problems of poor cycle stability and rate performance of water-based ion batteries are solved, and a new electrolyte with high ionic conductivity and low water reaction activity is achieved, which significantly improves the Electrochemical properties of NTP||LMO water-based ion batteries.
Patent Information
- Application Number
- CN202210280486.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-21
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-03-21
AI Technical Summary
The cycle stability and rate performance of water-based ion batteries are poor, mainly due to the side reaction between electrode materials and water-based electrolytes, which lead to capacity attenuation and electrochemical performance deterioration. The traditional high-concentration organic lithium electrolytes are unfriendly and costly, and are low. The cost electrolyte has low ionic conductivity.
A new electrolyte Li2SO4-Na2SO4-dodecyl sodium sulfate (SDS) mixed solution (LN-SDS-n) was designed, and a mixture of 0.5-1mol L-1Li2SO4 and 0.5-1mol L-1Na2SO4 was prepared by distilled water, and Add an appropriate amount of sodium dodecyl sulfate to form a transparent and bubble-free mixed liquid as an electrolyte solution, which is used to assemble NTP||LMO water-based ion battery, reduce water reaction activity and improve ionic conductivity.
Significantly improves the capacity retention rate and cycle stability of NTP||LMO water-based ion battery, with a capacity retention rate of 62-70% for 2000 cycles at room temperature, and excellent performance at low temperatures, with an ionic conductivity in the range of 13-93mS cm-1. , the electrochemical stability window is 1.78-2.06V, and the low-temperature performance is significantly improved.
Smart Images

Figure CN114695976B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical energy storage and relates to a method for improving the electrochemical performance of a NaTi2(PO4)3||LiMn2O4 aqueous ion battery. Background Art
[0002] Ion batteries using organic electrolytes are referred to as organic ion batteries, and ion batteries using aqueous electrolytes are referred to as aqueous ion batteries. Compared with organic ion batteries, aqueous ion batteries have the advantages of being environmentally friendly, having high rate performance, and having no safety hazards, and therefore have received widespread attention (Chem. Soc. Rev. 2020, 49, 180-232). However, due to the dissolution of electrode materials in aqueous electrolytes and their side reactions with aqueous electrolytes, the cyclic stability of aqueous ion batteries is poor (Nat. Chem. 2010, 2, 760-765; Energy Environ. Sci. 2016, 9, 3666-3673). For example, LiMn2O4 (LMO) is widely used as the positive electrode material of "rocking chair" aqueous lithium-ion batteries (Nano Energy 2020, 67, 104256), but LMO after delithiation can catalyze the oxygen evolution reaction of the electrolyte, reducing the upper voltage limit of the electrolyte, thereby leading to the deterioration of the performance of LMO-based batteries (J.Am.Chem.Soc.2010, 132, 11467-11469). As a NASICON-type compound, NaTi2(PO4)3 (NTP) is widely used as the negative electrode material of aqueous ion batteries (Mater.Today Energy 2020, 17, 100432-100452), but NTP contacts water and the capacity decays rapidly due to the self-discharge reaction, thereby leading to the deterioration of the performance of NTP-based batteries (Electrochim.Acta 2017, 235, 730-739.).
[0003] In order to improve the electrochemical performance of aqueous ion batteries based on NTP and LMO, researchers have developed a variety of methods. For example, surface modification of electrode materials (Electrochim.Acta 2017,255,220-229), reduction of particle size (Adv.Energy Mater.2013,3,290-294.), control of particle morphology (Nanoscale 2018,10,958-963), addition of additives that are conducive to the formation of electrode / electrolyte interface (Small 2020,16,2003585), etc. Among them, the research on aqueous ion battery electrolytes has received widespread attention (Adv.Energy Mater.2020,10,2001386).
[0004] Researchers have found that the use of "salt-in-water" (a concentrated electrolyte solution) electrolyte can effectively improve the cyclic stability of aqueous ions (Science 2015, 350, 938-943; Nat. Energy 2016, 1, 16129), which is attributed to the strong binding of high-concentration electrolytes with water molecules, reducing the reactivity of water in the electrolyte. The classic "salt-in-water" electrolyte is a high-concentration organic lithium salt (such as LiTFSI, LiBETI, LiOTf), which is not only expensive but also environmentally unfriendly, which limits its practical application (Nat. Energy 2019, 4, 269-280).
[0005] In order to solve this problem, researchers have developed molecular crowding effect electrolytes (Nat. Mater. 2020, 19, 1006-1011), ion polymer water (Nat. Commun. 2018, 9, 5320), local "salt water" (Angew. Chem. Int. Ed. 2021 2021, 60, 19965-19973), and low-cost saturated concentration alkali metal nitrates, sulfates, acetates and formates and other electrolytes (Energy Environ. Sci. 2018, 11, 2876-2883; Chem. Commun. 2019, 55, 12817-12820). The above electrolytes solve the problems of environmental unfriendliness and high cost of high-concentration fluoride electrolytes, but due to their low ionic conductivity, the rate performance of aqueous ion batteries using the above electrolytes is poor. Therefore, exploring new electrolytes with high ionic conductivity and low water reactivity is not only beneficial to improving the electrochemical performance of NTP||LMO, but also has important scientific significance. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a method for improving the electrochemical performance of NTP||LMO aqueous ion batteries.
[0007] A method for improving the electrochemical performance of NTP||LMO aqueous ion batteries, comprising the following steps:
[0008] 1) Use distilled water as solvent to prepare 0.5-1 mol L -1 Li2SO4 and 0.5-1mol L -1 Mixed solution of Na2SO4 VmL, obtain solution A;
[0009] 2) Add sodium dodecyl sulfate (SDS) to solution A, seal, stir at room temperature for 10 minutes, and then let stand until it becomes a transparent, bubble-free mixed solution to obtain a Li2SO4-Na2SO4-SDS mixed aqueous solution, abbreviated as LN-SDS-n;
[0010] 3) Using LN-SDS-n as the electrolyte, assemble the NTP||LMO aqueous ion battery.
[0011] NTP is the abbreviation of NaTi2(PO4)3, and LMO is the abbreviation of LiMn2O4.
[0012] Preferably, in step 2), the amount of SDS is 288.38×8.4×n×V / 1000, where 288.38 is the molecular weight of SDS, 8.4 is the critical micelle concentration (cmc) of SDS at room temperature, and n=30-120. Sealing is to prevent the electrolyte from absorbing moisture and falling into dust. The sealing step stabilizes the quality of the electrolyte.
[0013] The present invention designs a new electrolyte that can simultaneously reduce the water reaction activity and improve the ion conductivity, assembles an NTP||LMO aqueous ion battery, and the capacity retention rate and cycle stability are significantly improved.
[0014] The LN-SDS-n, wherein L represents lithium sulfate, N represents sodium sulfate, and n represents the concentration of SDS in the electrolyte at room temperature cmc (8.4 mmol L -1 , Biomacromol. 2019, 20, 4361-4369). Where n = 30-120.
[0015] Preferably, in step 1), the concentrations of lithium sulfate and sodium sulfate are both 0.5 mol L -1 .
[0016] Preferably, the steps of assembling the NTP||LMO aqueous ion battery using LN-SDS-n as the electrolyte are as follows:
[0017] a) taking appropriate amounts of electrode material powder, acetylene black and polyvinylidene fluoride, transferring them to an agate mortar, dropping appropriate amounts of N-methylpyrrolidone, and grinding them sufficiently to obtain a slurry; the electrode material powder comprises NTP powder and LMO powder; preparing an NTP working electrode with the NTP electrode material powder, and preparing an LMO working electrode with the LMO electrode material powder.
[0018] b) The slurry was uniformly coated on the current collector, and then placed in a vacuum drying oven and dried at 80° C. for 12 h to obtain a working electrode.
[0019] c) Assemble an R2032 button cell using the NTP working electrode as the negative electrode, the LMO working electrode as the positive electrode, LN-SDS-n as the electrolyte, and a separator between the positive and negative electrodes.
[0020] The LN-SDS-n has an ionic conductivity of 13-93 mS cm at -15°C to room temperature (25°C). -1 Its freezing point is -(3-4)℃. Its electrochemical stability window is 1.78-2.06V.
[0021] Preferably, the LN-SDS-n, wherein n=75-105; further preferably, the LN-SDS-n, wherein n=90.
[0022] Preferably, in step a), the mass ratio of the electrode material powder, acetylene black and polyvinylidene fluoride is 8:1:1.
[0023] Preferably, in step b), the current collector is a stainless steel mesh or a carbon cloth.
[0024] Preferably, in step b), the mass of NTP on the negative electrode of the working electrode is 2-3 mg cm -2 , the ratio of the mass of LMO on the positive electrode to the mass of NTP on the negative electrode is 13:12.
[0025] Preferably, in step c), the diaphragm is Whatman TM GF / A glass fiber paper or BH5510 sulfonated diaphragm.
[0026] Preferably, in step c), LN-SDS-n, wherein n=30, 60, 90 or 120.
[0027] Beneficial Effects
[0028] 1. The present invention improves the preparation method to significantly improve the capacity retention rate and cycle stability of the NTP||LMO aqueous ion battery based on LN-SDS-n. The NTP||LMO aqueous ion battery based on LN-SDS-n provided by the present invention cycles 600 times at room temperature 1C, 200 times at 2C, 400 times at 5C, and 800 times at 1C. After 2000 cycles, the discharge specific capacity is 28-47 mA h g -1 , the capacity retention rate is 62-70%.
[0029] 2. The NTP||LMO aqueous ion battery based on LN-SDS-90 obtained by the method of the present invention exhibits excellent electrochemical performance at low temperatures (0°C and -15°C); while the NTP||LMO using a Li2SO4-Na2SO4 mixed solution as the electrolyte cannot work at -15°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the LSV curve diagram of LN-SDS-n.
[0031] Figure 2 This is the ESW curve of LN-SDS-n.
[0032] Figure 3 This is the Raman spectrum of LN-SDS-n.
[0033] Figure 4 This is the conductivity curve of LN-SDS-n.
[0034] Figure 5 This is the differential scanning calorimetry curve of LN-SDS-n.
[0035] Figure 6 This is the freezable water content diagram of LN-SDS-n.
[0036] Figure 7 This is the molecular dynamics simulation diagram of LN-SDS-90 at room temperature.
[0037] Figure 8 This is the molecular dynamics simulation diagram of LN-SDS-0 at room temperature.
[0038] Fig. 9 For low temperature applied voltage (2V nm -1 ) under the action of LN-SDS-90 molecular dynamics simulation diagram.
[0039] Fig.10 This is the charge and discharge curve of NTP||LMO at room temperature and 0.2C.
[0040] Fig.11 This is the rate performance diagram of NTP||LMO at room temperature.
[0041] Fig.12 This is the cyclic stability diagram of NTP||LMO at room temperature.
[0042] Fig.13 This is the cycling stability diagram of NTP||LMO at 0℃, and the electrolyte is LN-SDS-90.
[0043] Fig.14 This is the cycling stability diagram of NTP||LMO at -15°C, and the electrolyte is LN-SDS-90. DETAILED DESCRIPTION
[0044] The technical solution of the present invention is further described below through specific embodiments in combination with the accompanying drawings. These embodiments are only for illustrating the technical solution of the present invention and cannot be regarded as limiting the content of the claims of the present invention.
[0045] Lithium sulfate, sodium sulfate, sodium dodecyl sulfate, and N-methylpyrrolidone in the examples were purchased from Shanghai Sinopharm Chemical Reagent Co., Ltd. TMGF / A glass fiber paper, acetylene black and polyvinylidene fluoride were purchased from Taobao Jinghong New Energy Online Store, stainless steel wire mesh was purchased from Shanghai Xing'an Screen Manufacturing Factory, carbon cloth was purchased from Taiwan Carbon Energy Technology Co., Ltd., BH5510 sulfonated diaphragm was purchased from Shenzhen Gebang Technology Co., Ltd., NTP was homemade according to the reference (J.Alloys Compd.2019,782,576-585), and LMO was purchased from Jining Wujie Technology Co., Ltd.
[0046] Raman spectrum was obtained by Renishaw inVia plus Raman spectrometer; differential thermal analysis was obtained by TA Instruments DSC2500 scanning differential calorimeter; rheological properties were obtained by TA DHR-2 interfacial rheometer; electrochemical properties of LN-SDS-n and NTP||LMO batteries were obtained by Shanghai Chenhua CHI760E electrochemical analyzer and Wuhan Lanhe CT2001A; theoretical simulation was calculated using GROMACS software package.
[0047] Example 1
[0048] The preparation steps of the traditional Li2SO4-Na2SO4 mixed electrolyte (LN-SDS-0) are as follows:
[0049] Using distilled water as solvent, prepare 0.5 mol L -1 Li2SO4-0.5mol L -1 Na2SO4 mixed solution 20mL,
[0050] LN-SDS-0.
[0051] Example 2
[0052] The preparation steps of LN-SDS-1 are as follows:
[0053] 1) Using distilled water as solvent, prepare 0.5 mol L -1 Li2SO4-0.5mol L -1 20 mL of Na2SO4 mixed solution to obtain solution A;
[0054] 2) Add 0.048 g SDS to solution A, seal, stir at room temperature for 10 minutes, and then let stand until it becomes a transparent, bubble-free mixed solution to obtain LN-SDS-1.
[0055] Example 3
[0056] The preparation steps of LN-SDS-30 are as follows:
[0057] 1) Using distilled water as solvent, prepare 0.5 mol L-1 Li2SO4-0.5mol L -1 20 mL of Na2SO4 mixed solution to obtain solution A;
[0058] 2) Add 1.45 g SDS to solution A, seal, stir at room temperature for 10 minutes, and then let stand until it becomes a transparent, bubble-free mixed solution to obtain LN-SDS-30.
[0059] Example 4
[0060] The preparation steps of LN-SDS-60 are as follows:
[0061] 1) Using distilled water as solvent, prepare 0.5 mol L -1 Li2SO4-0.5mol L -1 20 mL of Na2SO4 mixed solution to obtain solution A;
[0062] 2) Add 2.91 g of SDS to solution A, seal the container, stir at room temperature for 10 minutes, and then let it stand until it becomes a transparent, bubble-free mixed solution to obtain LN-SDS-60.
[0063] Example 5
[0064] The preparation steps of LN-SDS-90 are as follows:
[0065] 1) Using distilled water as solvent, prepare 0.5 mol L -1 Li2SO4-0.5mol L -1 20 mL of Na2SO4 mixed solution to obtain solution A;
[0066] 2) Add 4.36 g of SDS to solution A, seal, stir at room temperature for 10 minutes, and then let stand until it becomes a transparent, bubble-free mixed liquid to obtain LN-SDS-90.
[0067] Example 6
[0068] The preparation steps of LN-SDS-120 are as follows:
[0069] 1) Using distilled water as solvent, prepare 0.5 mol L -1 Li2SO4-0.5mol L -1 20 mL of Na2SO4 mixed solution to obtain solution A;
[0070] 2) Add 5.81 g of SDS to solution A, seal the container, stir at room temperature for 10 minutes, and then let it stand until it becomes a transparent, bubble-free mixed liquid to obtain LN-SDS-120.
[0071] Results Analysis
[0072] Figure 1 This is the room temperature linear sweep voltammogram of LN-SDS-n. Figure 1 It can be seen that the electrochemical stability window (ESW) of LN-SDS-n (n ≥ 1) is located at 1.78-2.06 V relative to the reversible hydrogen electrode, which is greater than 1.72 V of LN-SDS-0. Moreover, as n gradually increases, the ESW gradually increases to 2.06 V for LN-SDS-90 and then decreases to 2.02 V for LN-SDS-120 ( Figure 2 ). This is attributed to the formation of hydrogen bonds between the SDS head group and water molecules, which can reduce the reactivity of water molecules. LSV results show that the directional dynamics of water molecules in LN-SDS-n and the hydrogen bonds between the SDS head group and water molecules do not have a linear dependence on the SDS concentration.
[0073] Raman spectroscopy can reflect the reactivity of water molecules in the system. Figure 3 is the Raman spectrum of LN-SDS-n. Figure 3 It can be seen that when n ≥ 30, the spectrum appears at 2800-3000cm -1 The stretching vibration peaks attributed to CH3 and CH2 groups indicate the presence of SDS. Importantly, as n increases from 1 to 90, the peaks at 3000-3800 cm -1 The OH stretching vibration peak of LN-SDS-90 gradually decreases in intensity, while the OH stretching vibration peak intensity increases when n increases from 90 to 120. Raman spectroscopy results show that the reactivity of water in LN-SDS-90 is the lowest, which is consistent with the results of LSV.
[0074] The ionic conductivity of LN-SDS-n at room temperature to -15°C was tested by electrochemical impedance spectroscopy ( Figure 4 ).Depend on Figure 4 It can be seen that the conductivity of LN-SDS-n (n = 60, 90, 120) is significantly higher than that of LN-SDS-0 and LN-SDS-30, and is also significantly higher than that of the classic 21m LiTFSI "salt-in-water" electrolyte ( Figure 4 21 m LiTFSI was used for comparison). In addition, the room temperature conductivity of LN-SDS-n (n = 30, 60, 90, 120) (50-93 mS cm -1 ), and 10-40m HCOOK (46-130mS cm -1 , Chem. Commun. 2019, 55, 12817-12820), 10-30m of KOAc (32-90mS cm -1, Chem. Commun. 2019, 55, 12817-12820) and 25m LiNO3 (73.8mS cm -1 , Angew.Chem.Int.Ed.2021 2021,60,19965-19973) is comparable, and higher than other low-cost "salt-in-water" and molecular crowding effect organic fluoride electrolytes (0.8-25mScm -1 ,Nat.Mater.2020,19,1006-1011;Science 2015,350,938-943;Nat.Energy 2016,1,16129;ACS Energy Lett.2018,3,1769-1770). For specific comparison, see Table 1.
[0075] Table 1 Comparison of room temperature ionic conductivity of different electrolytes
[0076]
[0077] Importantly, the low temperature conductivity of LN-SDS-n (n = 30, 60, 90, 120) is excellent. For example, at -15°C, the conductivity of LN-SDS-n (n = 30, 60, 90, 120) is 13-17 mS cm -1 , while the conductivity of 25m LiNO3 at 10℃ is only 0.016mS cm -1 (Angew. Chem. Int. Ed. 2021 2021, 60, 19965-19973), there is no data reported for 25m LiNO3 at sub-zero temperatures. As the temperature decreases, the conductivity decreases, which is a general rule. Therefore, below zero degrees Celsius, the conductivity of LN-SDS-n (n = 30, 60, 90, 120) is much higher than that of 25m LiNO3.
[0078] Among LN-SDS-n (n=30, 60, 90, 120), LN-SDS-90 has the highest conductivity at different temperatures. This is because as n increases, the charge carrier concentration in the electrolyte increases, but the viscosity of the electrolyte also increases at the same time. Compared with LN-SDS-90, the lower conductivity of LN-SDS-120 is attributed to the increase in system viscosity, resulting in the binding effect of SDS micelles on cations exceeding the contribution of the increase in charge carrier concentration to conductivity.
[0079] The content of freezable water in aqueous electrolyte is an important indicator for evaluating its low-temperature (≤0℃) operation reliability. Figure 5 The LN-SDS-n differential scanning calorimetry curve is given. Figure 5It can be seen that as n increases by 30, the freezing point of the electrolyte decreases from -2.52°C of LN-SDS-0 to -4.03°C; and then as n increases, the freezing point of the electrolyte gradually increases to -3.07°C of LN-SDS-120. This shows that the addition of SDS is beneficial to lowering the freezing point of the electrolyte, but the decrease in the freezing point is not linearly related to the increase in SDS concentration. In addition, sodium sulfate and lithium sulfate in the system make important contributions to lowering the freezing point of the electrolyte. For example, the freezing point of SDS-90 (the electrolyte does not contain lithium sulfate and sodium sulfate, and the concentration of SDS is 90cmc) is -0.35°C, which is significantly higher than -3.71°C of LN-SDS-90. Therefore, the decrease in the freezing point of LN-SDS-n is attributed to the reaction between SDS and Li + / Na + and SO4 2- The synergistic effect of Figure 5 The data can be used to calculate the content of freezable water in the electrolyte. Figure 6 As shown, the variation trend of the freezable water content in LN-SDS-n is consistent with its freezing point; that is, the lower the freezable water content, the lower the freezing point of the electrolyte.
[0080] Although the freezing point of LN-SDS-n is not lower than -4.03℃, LN-SDS-n (n=30,60,90,120) still has high ionic conductivity at -15℃. To explain this experimental result, we performed molecular dynamics simulation using LN-SDS-90 as an example. The simulation results show that the SDS micelle clusters in LN-SDS-90 at room temperature are orderly arranged to form a directional ion transport channel ( Figure 7 ), while in LN-SDS-0, ions are randomly distributed in the electrolyte in the form of clusters at room temperature and cannot form qualitative ion transport channels ( Figure 8 ). At low temperature (-15-0℃), SDS and Li in LN-SDS-90 + / Na + and SO4 2- Ions are randomly distributed, and no directional ion transport channel is formed; under the action of electric field (0.5-2V nm -1 ), the SDS micelle clusters in LN-SDS-90 are orderly arranged to form a qualitative ion transport channel, and the charge carriers form a quasi-continuous ion flow in the channel ( Fig. 9 ), which ensures the high ionic conductivity of LN-SDS-90 at low temperatures.
[0081] Example 7
[0082] Assembly of NTP||LMO aqueous ion battery:
[0083] 1) Take appropriate amount of electrode material powder, acetylene black and polyvinylidene fluoride (mass ratio 8:1:1), transfer them to an agate mortar, add appropriate amount of N-methylpyrrolidone, grind them thoroughly, and prepare a slurry;
[0084] 2) The slurry was evenly coated on a stainless steel mesh (current collector), and then placed in a vacuum drying oven and dried at 80° C. for 12 h to obtain a working electrode.
[0085] 3) With NTP working electrode as negative electrode, LMO working electrode as positive electrode, LN-SDS-0 as electrolyte, Whatman TM GF / A glass fiber paper separator, assembled R2032 button cell.
[0086] Example 8
[0087] Assembly of NTP||LMO aqueous ion battery. The difference between Example 8 and Example 7 is that the electrolyte is LN-SDS-1.
[0088] Example 9
[0089] Assembly of NTP||LMO aqueous ion battery. The difference between Example 9 and Example 7 is that the electrolyte is LN-SDS-30 and the diaphragm is a BH5510 type sulfonated diaphragm.
[0090] Example 10
[0091] Assembly of NTP||LMO aqueous ion battery. The difference between Example 10 and Example 7 is that the electrolyte is LN-SDS-60 and the current collector is carbon cloth.
[0092] Embodiment 11
[0093] Assembly of NTP||LMO aqueous ion battery. The difference between Example 11 and Example 7 is that the electrolyte is LN-SDS-90 and the diaphragm is a BH5510 type sulfonated diaphragm.
[0094] Example 12
[0095] Assembly of NTP||LMO aqueous ion battery. The difference between Example 12 and Example 7 is that the electrolyte is LN-SDS-120 and the current collector is carbon cloth.
[0096] Results Analysis
[0097] Fig.10 LN-SDS-n is used as the electrolyte, NTP||LMO is at room temperature 0.2C (1C = 133mAg -1 ) under the charge and discharge curve. Fig.10It can be seen that when n is equal to 0, 1, 30, 60, 90, and 120, the discharge specific capacities of NTP||LMO are 59.4, 67.1, 62.8, 60.9, 65.1, and 55.6 mAh g, respectively. -1 Importantly, the coulombic efficiency of NTP||LMO charge and discharge is significantly improved when LN-SDS-n (n≥1) is used as the electrolyte, which means that LN-SDS-n (n≥1) can improve the reversibility of the electrode reaction. In addition, compared with LN-SDS-n (n=0,1,30,120), the discharge specific capacity of NTP||LMO at different current densities is significantly improved when LN-SDS-60 and LN-SDS-90 are used as the electrolyte, and it still has a high discharge specific capacity at 5C ( Fig.11 ). This shows that LN-SDS-60 and LN-SDS-90 can improve the rate performance of NTP||LMO.
[0098] Fig.12 is the room temperature cycling stability diagram of NTP||LMO. Fig.12 It can be seen that with LN-SDS-0 as the electrolyte, NTP||LMO was cycled 600 times at 1C, and the discharge specific capacity was 17.1 mA g -1 , the capacity retention rate is only 26.9%. However, with LN-SDS-n (n=60, 90, 120) as the electrolyte, the NTP||LMO discharge specific capacities were 40.5, 47.1 and 28.4 mA g-1 after 600 cycles of charge and discharge at 1C, 200 cycles at 2C, 400 cycles at 5C, and 800 cycles at 1C, for a continuous charge and discharge cycle of 2000 cycles. -1 , and the corresponding capacity retention rates are 61.9%, 70.4% and 66.2%, respectively. It can be seen that LN-SDS-n (n=60, 90, 120) can significantly improve the electrochemical cycling stability of NTP||LMO.
[0099] Fig.13 The cyclic stability diagram of NTP||LMO at zero degrees with LN-SDS-90 as the electrolyte. Fig.13 It can be seen that after 600 cycles at 1C, 1000 cycles at 2C, 2000 cycles at 5C, 1000 cycles at 2C, and 400 cycles at 1C, the NTP||LMO discharge capacity is 35.2 mA g -1 The capacity retention rate is 93.1%. Even after 200 cycles at 1C, 200 cycles at 2C, and 600 cycles at 1C at -15°C, and 1000 cycles continuously, the NTP||LMO discharge capacity is 10.7 mA g -1 , the capacity retention rate is 71.3% ( Fig.14 ), showing excellent low temperature cycling stability.
[0100] In summary, the present invention provides a method for improving the electrochemical performance of NTP||LMO aqueous ion batteries, that is, first designing a new aqueous electrolyte that can simultaneously improve ion conductivity and reduce water reactivity, and then assembling NTP||LMO aqueous ion batteries with this electrolyte. The provided NTP||LMO aqueous ion batteries can exhibit excellent electrochemical performance in the range of room temperature to -15°C.
Claims
1. A method for improving the electrochemical performance of NaTi2(PO4)3||LiMn2O4(NTP||LMO) aqueous ion battery, comprising the following steps: 1) Using distilled water as solvent, prepare 0.5 mol L -1 Li2SO4 and 0.5 mol L -1 Mixed solution of Na2SO4 V mL, solution A is obtained; 2) Add SDS to solution A, seal, stir at room temperature for 10 minutes, and then let stand until it becomes a transparent, bubble-free mixed solution to obtain LN-SDS-n; the LN-SDS-n has an ionic conductivity of 13-93 mS cm at -15 degrees Celsius to room temperature (25°C). -1 ; The amount of SDS used is 288.38×8.4×n×V / 1000, wherein 288.38 is the molecular weight of SDS, 8.4 is the cmc of SDS at room temperature, and n=90; 3) Using LN-SDS-n as the electrolyte, assembling the NTP∥LMO aqueous ion battery; the freezing point of the LN-SDS-n is -(3-4)°C; its electrochemical stability window is 1.78-2.06V; the SDS micelle clusters in the room temperature LN-SDS-90 are orderly arranged to form a directional ion transport channel.
2. The method for improving the electrochemical performance of NTP / / LMO aqueous ion battery according to claim 1, characterized in that: The steps of assembling the NTP∥LMO aqueous ion battery using LN-SDS-n as the electrolyte are as follows: a) taking appropriate amounts of electrode material powder, acetylene black and polyvinylidene fluoride, transferring them to an agate mortar, dropping appropriate amounts of N-methylpyrrolidone, and grinding them thoroughly to obtain a slurry; b) The slurry is evenly coated on the current collector, and then placed in a vacuum drying oven and dried at 80° C. for 12 h to obtain a working electrode; c) Assemble an R2032 button cell using the NTP working electrode as the negative electrode, the LMO working electrode as the positive electrode, LN-SDS-n as the electrolyte, and a separator between the positive and negative electrodes.
3. The method for improving the electrochemical performance of NTP / / LMO aqueous ion batteries according to claim 2, characterized in that: In step a), the mass ratio of electrode material powder, acetylene black and polyvinylidene fluoride is 8:1:
1.
4. The method for improving the electrochemical performance of NTP / / LMO aqueous ion battery according to claim 2, characterized in that: In step b), the current collector is a stainless steel wire mesh or a carbon cloth.
5. The method for improving the electrochemical performance of NTP / / LMO aqueous ion battery according to claim 2, characterized in that: In step b), the mass of NTP on the negative electrode is 2-3 mg cm -2 , the ratio of the mass of LMO on the positive electrode to the mass of NTP on the negative electrode is 13:
12.
6. The method for improving the electrochemical performance of NTP / / LMO aqueous ion battery according to claim 2, characterized in that: In step c), the diaphragm is Whatman TM GF / A glass fiber paper or BH5510 sulfonated diaphragm.
7. The method for improving the electrochemical performance of NTP / / LMO aqueous ion batteries according to claim 2, characterized in that: In step c), LN-SDS-n, wherein n=90.
Citation Information
Patent Citations
Electrode material of drainage rechargeable and dischargeable lithium ion and aqueous solution rechargeable and dischargeable lithium ion battery
CN102629686A
Rechargeable quinone-manganese oxide aqueous battery
CN105047933A
Novel water system secondary battery taking lithium salt and sodium salt as electrode materials
CN107180966A
Sodium ion total battery with super long cycle life and excellent low temperature performance
CN107887638A
Method for effectively preparing high-orientation and high-compactness two-dimensional material thin film
CN108568926A